Knowledge of women receiving healthcare service on the tasks of midwife working in the primary health care - Piechowska, Joanna; Iwanowicz-Palus, Grażyna; Bień, Agnieszka; Pieczykolan, Agnieszka (Nursing in the 21st Century, 2018)
KNOWLEDGE OF WOMEN RECEIVING HEALTHCARE SERVICE ON THE TASKS OF MIDWIFE WORKING IN THE PRIMARY HEALTH CARE Aim. The aim of the study was to determine the state of knowledge of women using health services on the midwife’s tasks in the primary health care. Material and methods. The research was conducted online in the period from February to March 2018 among women receiving health services in primary health care. The study was attended by 200 respondents aged 18-60 – they were informed about the voluntariness, anonymity of participation in research and the use of results only for scientific purposes. The diagnostic survey method was used for the research using the author’s questionnaire. Results. Most of the respondents knew their family physician (87.5%) and only half of the respondents knew their midwife (50%). The midwife was mainly associated with childbirth and neonatal care. In the minds of women, the midwife can conduct education (72%), but most of them only knew about the possibility of counseling in the field of pregnancy, postpartum period, early motherhood. Conclusions. 1. Women receiving healthcare services have incomplete knowledge of who their physician, midwife and nurse are in primary health care. 2. In the consciousness of women, there is the idea that midwives (including midwives of primary health care) deal only with pregnant women and after childbirth, but they do not know that midwives are involved in education regarding the prevention of gynecological diseases. 3. In reference to the low level of public knowledge about primary health care midwife’s competence, it is necessary to conduct activities aimed at promoting the midwife profession and raising public awareness in this area.